2010
DOI: 10.2224/sbp.2010.38.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of advertisements sent via mobile phone: Implications of the appeal, endorser, and involvement model and purchasing behavior

Abstract: In this study, the 3 dimensions of advertising strategy (Appeal, Endorser, Involvement) were unified to examine the effectiveness of advertising via a mobile phone (m-commerce). Participants viewed scenario based advertisements on a mobile phone then, via a survey, we measured the impact of advertising attitude, brand attitude, and purchase intention on 120 consumers as related to endorser and advertising appeal. Results indicated that consumers prefer emotional appeal presented by domestic endorsers for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…According to Setiadi (2003), indicators of purchase intention are interest, attitude of paying attention to the product, and the desire to buy based on needs. Purchase intention is a stage carried out by consumers before planning to buy a product (Yeh & In, 2010;Kotler, 2016;Rachbini, 2018). Based on this opinion, buying interest can be interpreted as a desire to buy which is part of the process leading to purchasing actions carried out by a consumer.…”
Section: Purchase Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Setiadi (2003), indicators of purchase intention are interest, attitude of paying attention to the product, and the desire to buy based on needs. Purchase intention is a stage carried out by consumers before planning to buy a product (Yeh & In, 2010;Kotler, 2016;Rachbini, 2018). Based on this opinion, buying interest can be interpreted as a desire to buy which is part of the process leading to purchasing actions carried out by a consumer.…”
Section: Purchase Intentionsmentioning
confidence: 99%
“…According to research by Yeh & In (2010) in an advertisement there is an influence of different types of endorsers on attitudes towards advertisements, attitudes towards brands and consumer purchase intentions. Although in another study conducted by Schouten et al (2020) revealed that there was no direct effect of the type of endorser on advertising and product attitudes, but there were several mediating effects through trust, similarity and identification which could explain the relationship between the type of endorser and advertising effectiveness.…”
Section: Type Of Endorsermentioning
confidence: 99%
“…Phau and Teah (2009) studied the motives of using SMS and its effect on SMS advertising acceptance. Yeh and Lin (2010) studied the effect of advertising appeal, the endorser, and the product involvement on attitude towards the ad. Very few studies explored antecedents beyond message-related attributes, or explored other factors related to communicating the SMS ad.…”
Section: Antecedents Of Short Message Service Advertising Acceptancementioning
confidence: 99%
“…Many factors were examined in the literature that influences the adoption of mobile marketing from both consumer and organizational perspectives; however, there is much inconsistency in literature and are fragmented (Roach, 2009). A review of the literature shows many probable factors, that have been discussed earlier, influence SMS advertising acceptance such as personal attitudes, perceptions and tendencies (Junglas et al, 2008;Bhatti, 2015;Khalifa & Shen, 2008), demographics (Bigne et al, 2005;Karjaluoto et al, 2008) social/peer influence (Kim et al,2008;Rohm & Sultan, 2006), acceptance of the mobile medium itself (Heinonen & Strandvik, 2007), Wireless Service Provider (WSP), brand trust (Zhang & Mao, 2008) and "ability to identify and utilize the individual consumer's purchasing behavior characteristics" (Yeh & Lin, 2010). There are several factors that affect consumer intention to adopt mobile marketing.…”
Section: Factors Of Mobile Marketingmentioning
confidence: 99%